Predation on black-footed ferrets (Mustela nigripes) and Siberian polecats (M. eversmannii): conservation and evolutionary implications - Biggins, Dean E., author; Wunder, Bruce A., advisor; Powell, Roger A., committee member; Andelt, William F., committee member; Detling, James K., committee member (Colorado State University. Libraries, 2000)
These studies were part of a conservation effort to develop efficient methods to reestablish free-ranging populations of endangered black-footed ferrets (Mustela nigripes) from a captive population. Behaviors critical to survival in the wild may be altered during generations of captivity. We conducted arena trials with four generations of captive-bred Siberian polecats (Mustela eversmannii) mustelids closely related to black-footed ferrets, and with a small sample of ferrets. Changes in the polecats' exploration of a novel arena and reaction to a predator model implied increased boldness through successive generations in captivity, which could increase predation rates on released animals. Releases of reproductively sterilized polecats in 1989-90 and the first release of black-footed ferrets in 1991 underscored the importance of predation; 46 of 92 radio-tagged ferrets and polecats were killed by predators. Quasi-natural rearing environments seemed to counteract some effects of captivity. Survival was highest for translocated wild-born polecats, followed by polecats reared in outdoor pens and in indoor cages respectively. Wild-caught polecats translocated from China had higher survival rates than captive-reared ferrets released onto native habitat, suggesting strong effects of captivity. Survival was 10-foId higher for pen-reared ferrets than for cage-reared ferrets at several release sites from 1992-1995. To reduce risk of predation, small mammals commonly avoid moonlight, but ferrets and polecats were most active during bright moonlight. The apparently canalized circadian activity pattern of ferrets may help them avoid diurnal raptors and their important canid predator, the coyote (Canis latrans). In arena trials with simulated attacks by a stuffed owl, pre-attack latency of departure from shelter was shorter than was postattack latency of departure for polecats, but not for ferrets. Compared to ferrets, polecats may rely more on risk assessment for decisions regarding timing of activity, induced by a temporally and spatially variable environment. In particular, plague (caused by Yersinia pestis) in Asia historically caused large fluctuations in populations of rodents, which may have favored prey-switching in polecats, increasing the complexity of their foraging/predator avoidance tradeoffs. The introduction of plague to western North America raises concerns regarding the highly specialized black-footed ferrets and their highly social prairie dog prey.
Keywords: ecology; forestry